NETIZENS' RESPONSE TO THE IKN ISSUE: A NETNOGRAPHY STUDY ON TEMPODOTCO 'S YOUTUBE CHANNEL BOCOR ALUS - Fadya Azizah Al Virandra; Kartikawati, Dwi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the response of netizens to the issue of moving the National Capital City (IKN) in the episode "The Fate of the IKN in the Hands of Prabowo and Jokowi's Evaluation of the Head of the IKN, from Land Issues to Investment" on TempoDotCo 's YouTube channel Bocor Alus Politik. Through a nethnography approach, this study examines the comments of netizens in response to the issue, revealing various expressions of digital politics, social identity, and criticism of public policy. Using the Public Sphere theory, and media equation theory, this study highlights the dynamics of interaction between satirical media, public opinion, and digital political participation. he results of the study indicate that netizens' comments serve not only as a means of political expression but also as a reflection of collective negotiation and public discourse surrounding IKN policies. The findings indicate three predominant patterns in netizens' opinions. The first is a rejection of the IKN project, encompassing controversies over its development, concerns regarding its potential impacts, and widespread public skepticism. Second, the perspective of governance and leadership, including the management of the capital city and the political situation of Indonesia. and the third development project of the capital city is considered good which includes community support. This research contributes to a new understanding of digital political literacy and the importance of social media platforms in shaping contemporary political discourse. The novelty of this research lies in the use of nethnography to examine public responses in the context of satirical media, which is rarely the focus of political communication studies.